Creating, Sustaining, and Contesting Definitions of Reality: Marcus Tullius Cicero as a Pragmatist Theorist and Analytic Ethnographer - Prus, Robert (Qualitative Sociology Review, 2010)
Although widely recognized for his oratorical prowess, the collection of intellectual works that Marcus Tullius Cicero (106-43 BCE) has generated on persuasive interchange is almost unknown to those in the human sciences. Building on six texts on rhetoric attributed to Cicero (Rhetorica ad Herennium, De Inventione, Topica, Brutus, De Oratore, and Orator), I claim not only that Cicero may be recognized as a pragmatist philosopher and analytic ethnographer but also that his texts have an enduring relevance to the study of human knowing and acting. More specifically, thus, Cicero's texts are pertinent to more viable conceptualizations of an array of consequential pragmatist matters. These include influence work and resistance, impression management and deception, agency and culpability, identity and emotionality, categorizations and definitions of the situation, and emergence and process.